(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses small business and private entrepreneurship in the Republic of Uzbekistan, its current issues in public life, the tax system in the legislation on small business and entrepreneurship, the laws adopted in the field of this activity since independence and amendments to them.